2021
DOI: 10.1111/jvim.16326
|View full text |Cite
|
Sign up to set email alerts
|

Performance of lymph node cytopathology in diagnosis and characterization of lymphoma in dogs

Abstract: Background Cytopathology is a minimally invasive and convenient diagnostic procedure, often used as a substitute for histopathology to diagnose and characterize lymphoma in dogs. Objectives Assess the diagnostic performance of cytopathology in diagnosing lymphoma and its histopathological subtypes in dogs. Animals One‐hundred and sixty‐one lymph node samples from 139 dogs with enlarged peripheral lymph nodes. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 20 publications
1
9
0
1
Order By: Relevance
“…Consequently, a high number of phenotypic aberrancies would be lost performing only IHC. Still, histopathology plus IHC remains the gold standard technique to classify canine lymphoma according to the WHO system [37]. Thus, we support the concomitant use of FC and IHC for more detailed characterization of canine lymphoma cases.…”
Section: Discussionsupporting
confidence: 67%
“…Consequently, a high number of phenotypic aberrancies would be lost performing only IHC. Still, histopathology plus IHC remains the gold standard technique to classify canine lymphoma according to the WHO system [37]. Thus, we support the concomitant use of FC and IHC for more detailed characterization of canine lymphoma cases.…”
Section: Discussionsupporting
confidence: 67%
“…Cell size as assessed by cytology can be a useful indicator that neoplastic cells are present but should not be used to predict biological behavior. A study assessing the performance of cytology to diagnose and characterize lymphoma in dogs revealed that cytology is useful in accurately diagnosing lymphoma, but accuracy decreases when attempting to predict grade and phenotype, and ancillary diagnostics must be used for further characterization 34 . The cases in this study had small cell size defined by flow cytometry FS.…”
Section: Discussionmentioning
confidence: 86%
“…A study assessing the performance of cytology to diagnose and characterize lymphoma in dogs revealed that cytology is useful in accurately diagnosing lymphoma, but accuracy decreases when attempting to predict grade and phenotype, and ancillary diagnostics must be used for further characterization. 34 The cases in this study had small cell size defined by flow cytometry FS. Though only 4 cases had histology, all 4 had lymphocytes described as small to intermediate in size.…”
Section: Clinical Outcome and Survival Analysismentioning
confidence: 76%
“…Nos cães, o linfoma é comumente classificado com base nos achados citológicos, sendo a análise citopatológica de grande valia no diagnóstico de linfoma em cães (Martini et al, 2022). Duas principais classificações são utilizadas para o LC:…”
Section: Discussionunclassified